Molecular Docking and Physicochemical Profiling of Selected Natural Phenolics for Supporting Color Stability in Goat Meat - Hussein, Uday Abdul Reda; Hamad, Mohammed Haider; Khudhur, Hasan Raheem; Bayati, Suhail; jado aa, Khudair Abbas; Gati, Mohannad Abdulrazzaq; hisham, Ghasan (Journal of Meat Science, 2026)
Stability of meat color is an important quality trait that impacts consumer acceptance of fresh meat products. The oxidative transformation of myoglobin to metmyoglobin is the major cause of color deterioration throughout storage. Natural phenolic compounds have gained interest as potential antioxidants and can play a role in stabilizing the pigment proteins, consequently prolonging oxidative processes. This study used molecular docking and physicochemical profiling to evaluate the interaction of gallic acid, naringenin, and rosmarinic acid with metmyoglobin (PDB ID: 1YMB). In this study the computational model was used to simulate docking, assess binding affinity and interaction modes at the heme-associated pocket of protein has been done by AutoDock Vina. The observed order of binding energies followed the results as rosmarinic acid (–6.7 kcal/mol) > naringenin (–6.0 kcal/mol) > gallic acid (–4.6 kcal/mol), revealed to a greater interaction potential when comparing larger polyphenolic structures. Analysis of the interaction showed that rotamer rotations of ligands made hydrogen bonding and electrostatic contacts with important residues near to the binding pocket, including Asp109, His113, Ile112, Arg31 and Arg139. SwissADME analysis using for physicochemical properties of the compounds, also indicated differences between each compound; gallic acid was found to have very polar, high solubility properties, which were confirmed by the naringenin molecule which demonstrated balanced lipophilicity without being too headache inducing and rosmarinic acid displayed having optimal hydrogen bonding capacity and molecular size. These results offer a molecular level basis for considering the application of natural phenolic compounds as a means to augment pigment stability within meat systems, though experimental confirmation is needed in order to assess practical applicability.